A snapshot of Snf2 enzymes in fission yeast. (20th November 2013) - Prasad, Punit; Ekwall, Karl
Abstract : Eukaryotic chromatin is remodelled by the evolutionarily conserved Snf2 family of enzymes in an ATP-dependent manner. Several Snf2 enzymes are part of CRCs (chromatin remodelling complexes). In the present review we focus our attention on the functions of Snf2 enzymes and CRCs in fission yeast. We discuss their molecular mechanisms and roles and in regulating gene expression, DNA recombination, euchromatin and heterochromatin structure.